Perancangan Sistem Informasi Penggajian Karyawan Pada Tb Blitar Berbasis User Centered Design - Bastyan Fahri Siswanto; Perani Rosyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Employee payroll is the most important system in a company, in collecting employee payroll data real data collection is needed so that there are no errors in administration. In this study, the payroll of employees at the Blitar Building Shop which provides building tools and building materials still uses a manual system which results in the administration being less efficient in the use of time. And this research the author produces an application design Employee Payroll Information System. This payroll information system is designed using the waterfall method, the waterfall method is the process of making a system that is structured and has several stages that must be passed in its manufacture. This employee payroll information system was created with the aim of facilitating the administration in carrying out their duties. Among other things, input data on basic salary, overtime salary, deductions. The payroll information system is a development from the previous manual system using handwriting to a web-based application. This payroll information system is efficient because the user interface is very easy to understand and web-based. It is hoped that this application can be more accurate and facilitate the calculation of employee salaries